Hepatoprotective and Hematoprotective Effects of Vitamin C Against Paracetamol Toxicity in Wistar Albino Rats - elmatoni, Wafa; Sidoun, Mustafa; Shabash, Alhammaly (The Libyan Journal of Science, 2024)
Paracetamol is a commonly prescribed analgesic and antipyretic medication with potentially lethal side effects when used in large doses. The current experiment sought to determine if vitamin C (ascorbic acid) alleviates the hepatotoxicity and Hematotoxicity induced by paracetamol in rats. 36 male rats were divided into four groups: control group; paracetamol group (APAP 400 mg/kg, orally); vitamin C treated group (200 mg/kg, orally); vitamin C-paracetamol treated group (vitamin C 200 mg/kg orally and APAP 400 mg/kg orally). The findings of this study showed that paracetamol administration significantly elevated the liver enzymes (AST and ALT), WBCs and MCHC values while significantly reduced the MCV level. Vitamin C restored the AST, ALT levels and WBCs count nearly to their normal levels and reverse the paracetamol effects on hematological markers. The current study’s findings show that vitamin C greatly reduces PCM-induced hepatotoxicity while only slightly protecting against hematotoxicity.